Strategies for Reducing and Preventing Anemia in Pregnant Women: Systematic Literature Review - Isabelita Madeira Soares; Artur Natalino Corte Real Araújo; Natalia Pereira (PT. Banjarese Pacific Indonesia, 2024)
Anemia in pregnant women is a serious health problem with negative impacts on the health of the mother and fetus. The aim of this research is to conduct a literature review on strategies for reducing and preventing anemia in pregnant women. This study used the Systematic Literature Review (SLR) method to collect and evaluate 20 relevant articles regarding strategies for reducing and preventing anemia in pregnant women. A literature search was conducted through various databases and articles that met the inclusion and exclusion criteria were selected for analysis. The main finding of this literature review is that several effective strategies have been identified for the reduction and prevention of anemia in pregnant women, including iron and folic acid supplementation, dietary changes, regular check-ups, health education, and community-based awareness campaigns. Factors such as public awareness, supportive health policies, and easy access to health services play an important role in supporting the successful implementation of these strategies. However, there are also obstacles such as limited access and resources, non-compliance, and cultural challenges that can hinder efforts to prevent anemia. The conclusion of this research is that strategies for reducing and preventing anemia in pregnant women require a holistic approach involving various aspects, including strengthening health services, targeted health education, and cross-sector collaboration. By implementing appropriate recommendations, it is hoped that a significant reduction in the prevalence of anemia in pregnant women can be achieved and improve the overall health of mothers and fetuses.